Charlotte Todes Stern, Staff Member of the Workers' Health Bureau: "We Were in Advance of Our Time". (November 2014) - Baxandall, Rosalyn; Dunn, Mary Lee; Slatin, Craig
Charlotte Todes Stern (5/5/1897-11/15/1996) was a radical activist for most her life, beginning with her introduction to YPSL (Young People's Socialist League) during her college years. In 1923, Todes Stern became a staff member of the Workers' Health Bureau (WHB), and two years later she became their Organizing Secretary. She traveled the United States organizing for the WHB until 1927. This is the third of seven interviews with Charlotte Todes Stern, conducted by Rosalyn Baxandall for the Feminist History Research Project. This interview focuses on the Workers' Health Bureau, its formation, early efforts with the Painters' union in New York, its accomplishments and efforts to obtain safer and healthier working conditions for workers throughout industry, and its organization of annual national conferences for occupational health and safety. Todes Stern discusses the conflicts with the American Federation of Labor and the demise of the Bureau. An interview with Grace Burnham McDonald appears on page 327 of this issue.